The digital transformation of the public sphere - Santos, T.; Louçã, J.; Coelho, H. (Systems Research and Behavioral Science, 2019)
In this paper, we study the relationship between social media and traditional media and their impact on democratic systems. We revisit the concepts of the public sphere and agenda-setting and translate them into the current media landscape. Using topic-modeling techniques, we then explore the effects of first level agenda-setting in the Twitter debate on the Brexit referendum. Our results reveal a complex dynamics in the transmission of the media agenda to the public agenda. The traditional media dominated the debate, but not entirely, as alternative media played an important role in the campaign. The "Leave" campaign had more success in the transmission of its interpretative agenda, while the user-generated content polarized the media's message. We conclude with a list of recommendations to address the societal challenges posed by the transformation of the media environments.